Menyibak Penentuan Harga Jual Bakso Keliling Menggunakan Strategi Mangkuk Di Kelurahan Sentul Blitar - Indarryanti, henni; Suprianto , Suprianto; Rostianing , Ika (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2024)
This research focuses on Micro, Small and Medium Enterprises(MSMEs) in the food sector, such as mobile meatball traders in Sentul Village,Blitar City. This traveling meatball seller sells along the roads passes whiletraveling by visiting potential buyers directly. This traders, with all theirsimplicity and limitations, appear to have no small potential and role in nationaldevelopment. Therefore, the aim of this research is to determine the selling pricesof mobile meatball traders using the bowl strategy in Sentul Blitar Village.This research uses a type of qualitative research using 4 (four) datacollection techniques in the form of observation, interviews, documentation andliterature studies where the results of data collection can be analyzeddescriptively.The results of this research show that mobile meatball traders sell theirwares using the bowl strategy. This means that traders free buyers to buy theirmerchandise at any nominal amount as long as supplies are still available. Withthe strategy used, it is possible to estimate the profit earned by a travelingmeatball seller if all his merchandise is sold. It is estimated that from sellingthese meatballs, traders can earn a profit of Rp. 260.0444,- per day.